2023
DOI: 10.1101/2023.01.30.23285067
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Diagnostic and Triage Accuracy of the GPT-3 Artificial Intelligence Model

Abstract: Importance: Artificial intelligence (AI) applications in health care have been effective in many areas of medicine, but they are often trained for a single task using labeled data, making deployment and generalizability challenging. Whether a general-purpose AI language model can perform diagnosis and triage is unknown. Objective: Compare the general-purpose Generative Pre-trained Transformer 3 (GPT-3) AI model's diagnostic and triage performance to attending physicians and lay adults who use the Internet. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 37 publications
1
51
2
Order By: Relevance
“…The diagnostic accuracy of the GPT-3 model is considerably limited. A preprint article revealed the correct diagnosis to be 88% within the three differential-diagnosis lists [ 30 ]. Therefore, the diagnostic accuracy of the differential-diagnosis lists generated by AI chatbots, including ChatGPT-3, is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic accuracy of the GPT-3 model is considerably limited. A preprint article revealed the correct diagnosis to be 88% within the three differential-diagnosis lists [ 30 ]. Therefore, the diagnostic accuracy of the differential-diagnosis lists generated by AI chatbots, including ChatGPT-3, is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…15 Recently, there has been great interest in utilizing the nascent but powerful chatbot for clinical decision support. 1618…”
Section: Introductionmentioning
confidence: 99%
“…A very encouraging triage accuracy of 87.2% in our study stands in contrast to recent results on the non-ophthalmological general medical domain published in a preprint by Levine and colleagues, who found a triage accuracy of 71% for GPT-3 and 96% for physicians. [7] Whether this contrast is due to the different testing domains, wording of the individual vignettes or an improvement between the different GPT versions remains unclear. Moreover, we must point out, that a technically high triage accuracy does not imply a great utility of the information on urgency: In our study ChatGPT frequently recommended to consult a physician "as soon as possible", which was judged to be appropriate for the urgency levels "emergency" and "same day".…”
Section: Discussionmentioning
confidence: 99%
“…Triage accuracy however was slightly and insignificantly lower compared to laypersons but by far and significantly lower compared to physicians. [7] For "can't-miss diagnoses", the aforementioned study from the Wills Eye emergency department showed a diagnostic accuracy of triaging ophthalmology staff to be as high as 97.2%. [11] We therefore clearly recommend contacting established providers of ophthalmological emergency services in case of acute symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation